2002
DOI: 10.1096/fj.01-0994fje
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence that a human antibody derived from patient serum can promote myelin repair in a mouse model of chronic‐progressive demyelinating disease

Abstract: Certain human sera from patients with monoclonal gammopathies contain factors that induce myelin repair in animals with demyelinating disease. We hypothesize that antibodies functionally distinguish the serum of one patient from another. However, pooled normal polyclonal human IgM antibodies also induce remyelination. Definitive proof that specific antibodies are the biologically active components of serum is missing because unquestionably pure preparations of antibody molecules cannot be generated by fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 15 publications
1
70
0
Order By: Relevance
“…For instance, upregulation of the local adaptive immune response in SOD1 G93A mice with Copaxone (glatiramer acetate) vaccination eliminates destructive self-compounds associated with motor neuron death resulting in protection of motor neurons and extension of the life span of the animals. In addition, numerous studies have reported a protective role of the fine-tuned adaptive immune response (Warrington et al, 2000;Bieber et al, 2001;Kriz et al, 2002;Mitsunaga et al, 2002;Nguyen et al, 2002;Schenk, 2002;Wyss-Coray and Mucke, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, upregulation of the local adaptive immune response in SOD1 G93A mice with Copaxone (glatiramer acetate) vaccination eliminates destructive self-compounds associated with motor neuron death resulting in protection of motor neurons and extension of the life span of the animals. In addition, numerous studies have reported a protective role of the fine-tuned adaptive immune response (Warrington et al, 2000;Bieber et al, 2001;Kriz et al, 2002;Mitsunaga et al, 2002;Nguyen et al, 2002;Schenk, 2002;Wyss-Coray and Mucke, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Antimyelin component antibodies generated under pathological conditions might have either adverse or beneficial effects (van der Veen et al, 1986(van der Veen et al, , 1989Endoh et al, 1986;Sadler et al, 1991;Potter and Stephens, 1994;Genain et al, 1995;Laman et al, 2001;Morris-Downes et al, 2002;Mitsunaga et al, 2002;Schwab, 2004). Moreover, potential pathogenetic roles for antimyelin antibodies, including anti-PLP antibodies, have been suggested in MS (Sun et al, 1991;Warren et al, 1994;Sellebjerg et al, 1995Sellebjerg et al, , 2000Archelos et al, 2000;Carvalho et al, 2003;Berger et al, 2003;Qin et al, 2003;Kanter et al, 2005;Zhang et al, 2005a).…”
Section: Implications For Msmentioning
confidence: 99%
“…rHIgM22 and rHIgM12 are recombinant human IgMs generated by expression cell lines constructed by our team [20,21] and purified to greater than 97% purity using a 3 step column procedure, CHT Ceramic Hydroxyapatite, Type II (Bio-Rad), a CIM QA-8f Monolithic column (BIA Separations) and a Sephacryl S-300 HR column [10]. The final IgMs were validated using titrated potency assays of binding to the surface of live neurons, oligodendrocytes and tissue slices or the support of neurite extension.…”
Section: Human Recombinant Antibodiesmentioning
confidence: 99%